Penerapan Customer Relationship Management (CRM) pada Bengkel Jasa Servis Sepeda Motor: Studi Kasus pada Bengkel di Kota Bogor - Merli Mai Damayanti; Titiek Tjahja Andari (MANAJEMEN, 2026)
This study aims to analyze the implementation of Customer Relationship Management (CRM) in a motorcycle service workshop, focusing on customer interaction and customer relationship maintenance. A descriptive qualitative approach was used, with data collected through observation, interviews, and discussions. The results indicate that customer data management has been implemented adequately; however, it has not been optimally utilized to support continuous communication. Customer interaction is considered moderately effective, as it mainly occurs during the service process and is not consistently maintained afterward. Meanwhile, customer relationship maintenance remains suboptimal due to the absence of systematic follow-up and complaint recording. This study proposes a customer complaint form as a practical solution to improve service quality and strengthen long-term customer relationships.